2021
DOI: 10.7150/jca.50868
|View full text |Cite
|
Sign up to set email alerts
|

Data mining analysis of the prognostic impact of N6-methyladenosine regulators in patients with endometrial adenocarcinoma

Abstract: We reanalyzed the expression of 16 acknowledged N 6 -methyladenosine (m 6 A) RNA regulators in 406 endometrial adenocarcinoma patients and 19 controls using The Cancer Genome Atlas (TCGA) dataset, and further verified our results using Gene Expression Omnibus (GEO) dataset and real-time quantitative polymerase chain reaction. Thirteen m 6 A RNA methylation regulators were differentially expressed between patients with endometrial adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The expression of KIAA1429 observed in EC was significantly decreased, leading to the reduction of m6A levels [84]. KIAA1429 gene expression is associated with cellular nucleic metabolism.…”
Section: Endometrial Cancermentioning
confidence: 98%
“…The expression of KIAA1429 observed in EC was significantly decreased, leading to the reduction of m6A levels [84]. KIAA1429 gene expression is associated with cellular nucleic metabolism.…”
Section: Endometrial Cancermentioning
confidence: 98%
“…FTO, RBM15, and YTHDF1 were identified as independent prognostic markers for endometrial cancer, and FTO and RBM15 were differentially expressed between endometrial adenocarcinoma and hyperplasia. These data suggest that FTO, RBM15, and YTHDF1 are critical in the progression and prognosis of endometrial cancer (82,97). Interestingly, Zhang et al found that CpG sites located at the m 6 A regulatory site may be considered a potential prognostic feature of endometrial cancer patients (98).…”
Section: Prognostic Effect Of M 6 a Rna Methylation Regulators On End...mentioning
confidence: 92%
“…According to Zhai et al ( 142 ), RBM15/15B, YTHDF1 and IGF2BP1/2 are upregulated in endometrial adenocarcinoma. By contrast, FTO, KIAA1429, METTL14, ZC3H13 and YTHDC1 expression was downregulated.…”
Section: M6a and Ecmentioning
confidence: 99%